Your comments matter: incorporating viewers' comments for ranking online video content using bibliometrics. Issue 4 (2nd October 2018) - Mirza, Naveed Aslam; Khan, Hikmat Ullah; Iqbal, Tassawar; Iqbal, Khalid; Iqbal, Saqib; Imran, Muhammad
ABSTRACT: The quality of user-generated content over World Wide Web media is a matter of serious concern for both creators and users. To measure the quality of content, webometric techniques are commonly used. In recent times, bibliometric techniques have been introduced to good effect for evaluation of the quality of user-generated content, which were originally used for scholarly data. However, the application of bibliometric techniques to evaluate the quality of YouTube content is limited to h -index and g -index considering only views. This paper advocates for and demonstrates the adaptation of existing Bibliometric indices including h -index, g -index and M -index exploiting both views and comments and proposes three indices h vc, g vc and m vc for YouTube video channel ranking. The empirical results prove that the proposed indices using views along with the comments outperform the existing approaches on a real-world dataset of YouTube.